Faktor Pengaruh Harga Saham dengan Pendekatan Analisis Rasio - Shintya Hanika Surahmansyah (Universitas Katolik Indonesia Atma Jaya, 2020)
Factors related to the condition of the company are generally indicated in the financial statements, which is one measure of company performance. Fundamental analysis is a factor often used to predict stock prices. This study aims to determine the effect of Earning per Share (EPS), Return on Equity (ROE), and Net Profit Margin (NPM) on the stock prices of financial institutions listed on the Indonesia Stock Exchange in 2015-2018. The population in this study is the company of financial institutions listed on the Indonesia Stock Exchange in 2015-2018. The sample in this study is 10 companies and the selection of ampples using purposive sampling method. The analytical method used is multiple linear analysis method. The results of the analysis conducted indicate that EPS partially influences the stock price while ROE and NPM do not affect the stock price. Simultaneous in test shows the results that together EPS, ROE, and NPM affect the stock price. From the test determination coefficient results obtained 57.6% changes in stock prices are influenced by EPS, ROE, and NPM factors. While the remaining 42.4% is influenced by other factors.